Implementation of VOIP (Voice Over Internet Protocol) at Bhayangkara Hospital Bengkulu - Yosi Asniar Yani; Maryaningsih Maryaningsih; Yode Arliando (Penerbit Jurnal Indonesia, 2021)
In communication technology, voice communication is something that will be a very important part, because currently voice communication is considered the most practical communication. Bhayangkara Bengkulu Hospital is one of the Government Hospitals engaged in the health sector in Bengkulu Province. So far in communicating, Bhayangkara Bengkulu Hospital is still simple and communication media is still limited. Communication media between officers still uses HT and HP, because only a few rooms use telephones. The purpose of this research is to build a VoIP network at Bhayangkara Bengkulu Hospital so that it can facilitate communication at Bhayangkara Bengkulu Hospital. VoIP implementation at Bhayangkara Bengkulu Hospital is made using Mikrotik RB951 and Trixbox which is placed on a computer that will be used as a server. The Zoiper application is installed on each computer in each treatment room and other agencies. The functionality of this VoIP network makes it easier and can help the Bhayangkara Bengkulu Hospital in communicating. This system has been tested and the results are satisfactory as desired, although there are still obstacles in the practice of using it